Covid 19 Stress and Teaching Performance of Social StudiesTeachers in Public Higher Educational Institutions in Zambales - Decena, Venzeil F (South Asian Journal of Social Sciences and Humanities, 2023)
This study sought to establish a baseline for a faculty stress management program by assessing the COVID 19 stress levels of social studies teachers at public higher education institutions in Zambales in relation to their teach performance throughout the pandemic. The results showed that there were 34-year-old female Social Studies teachers who were single, earns a Salary Grade 11 to 13, and have 0 to 3 years of experience in the field. According to the respondent’s self-evaluation, they have high levels of COVID 19 Stress and rank the subscale COVID Danger and Contamination Fear as their top stressor. However, they are less likely to experience COVID Traumatic Stress Symptoms, which only cause moderate stress. The responders’ performance throughout the academic year 2020–2021 was Very Satisfactory. However, there is no correlation between respondents’ COVID 19 stress levels and their teaching performance. Moreover, there is no significant difference between the COVID 19 stress level of the respondents when grouped according to their age, gender, civil status and number of years in service. However, there is significant difference between the COVID 19 stress levels of the respondents when grouped according to their economic status. Given the study’s preceding findings, these must be verified and further explored in future studies involving a younger and larger population due to exposure to social media. Additionally, it is urged that these workers from various fields incorporate mental health promotion as a follow-up service after the outbreak of the COVID 19 epidemic.